Nonlinear FEA of Soil-Structure-Interaction Effects on RC Shear-Wall Structures - Saadi, Dina (My University, 2018)
Support condition is a crucial input to any structural model which influences the system’s behavior. Soil-structure interaction (SSI) evaluates system’s response while accounting for the soil as the base. Unlike the conventional rigid support condition, SSI takes into account soil characteristics that determine its strength and flexibility. Systems that consider SSI are called flexible base systems, while systems that use full fixity restrains are called fixed base systems. This research will analyze flexible base systems under variable parameters. These parameters are related to the soil and to the structure. Soil parameters include shear wave velocity, shear modulus, bearing capacity and stiffness. Structure parameters include number of stories, seismicity design levels, and reinforcement detailing. The structure that is going to be analyzed is a multi-story concrete structure with shear walls and gravity columns. Soil medium as well as foundations is going to be modeled to capture SSI effects. 3D finite element modeling is to be performed along with nonlinear pseudo-static analysis. Shear walls, foundations, and soil medium are to be modeled using 3D brick element to accurately capture the system behavior. After validating the modeling technique, models with different variables are going to be compared in terms of stresses, strains, moments, drifts, base shears and damage levels.
Keywords: Soil Structure Interaction; Reinforced Concrete; Cyclic Loading; Nonlinear Modeling; Shear Walls; Seismic Assessment